Habits and Preferences of Consumption of People Diagnosed with Depression - Melo, Francisco Vicente Sales (2018)
Objective: Studies relating depression and consumption of products in general are still incipient in the consumer behavior literature. With this, the objective of this research was to identify the consumption habits and preferences of individuals diagnosed with some level of depressive disorder. Method: Through a survey, 451 participants answered items related to depression and the consumption of goods and services distributed in twelve categories. To check if the participants had any level of depression, the Beck Depression Inventory (BDI) was applied. Originality/Relevance: Studies that could indicate a profile of the habits of consumption of people with depression were not seen in the literature, since they generally present relatively different or more frequent behaviors of those who do not have the disease, due to their symptoms. With this, it is noticed that there is a theoretical gap in studies that evaluate the effects that this disorder can generate in the general habits and preferences of consumption and in what way the companies can develop actions that improve the well-being of these people. Results: The results revealed that 26.2% of respondents presented some level of depression. It was found that there is a relationship between depression and some specific habits and consumption preferences, which characterizes a specific profile of consumers. Theoretical/methodological contributions: This study contributes to the consumer behavior literature by presenting a frame with more frequent profile, habits and preferences of people with depression, besides pointing out practical possibilities for the development of public and business policies, for the well-being of these individuals in society.